PENERAPAN MODEL PEMBELAJARAN PROJECT-BASED LEARNING (PJBL) DALAM MENINGKATKAN KEPEDULIAN LINGKUNGAN PADA SISWA KELAS III SD - Aulia Ismiyani Mubariqoh; Kms. Muhammad Amin Fauzi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to implement the Project-Based Learning (PjBL) model to increase environmental awareness among third-grade elementary school students through the topic of Environmental Pollution in science. The activity took place at the SDN 1 Girikarto Technical Implementation Unit (UPTD) from October 13–17, 2025, involving 22 students. The implementation method consisted of three main stages: (1) introducing the concept of environmental pollution through discussions, educational videos, and questions and answers; (2) implementing an environmental campaign poster project in groups; and (3) presenting the results and concrete actions to maintain a clean school environment. Assessment procedures included process observation, feedback during the activity, and summative assessment of the product and presentation. The implementation results showed that PjBL increased student motivation, creativity, and active engagement. Students appeared enthusiastic in collaborating on the project, discussing it, and expressing ideas related to environmental protection efforts. Furthermore, project-based learning provided authentic experiences that encouraged students to think critically and responsibly about their surroundings. The main obstacle, limited project time, was overcome by adding additional time outside of class hours. Overall, the implementation of the PjBL model is effective in fostering environmental awareness and increasing understanding of the concept of pollution in elementary school students.